Adapting Pancasila Education for the Digital Age: Hybrid Training Challenges and Opportunities - Lutfi , Fuad; Yulianto, Arief; Pramono, Suwito Eko; Masrukhi, Masrukhi (Proceedings of International Conference on Science, Education, and Technology, 2024)
This study explores the adaptation of Pancasila education for the digital age through hybrid training models, addressing the challenges and opportunities in this context. Pancasila, Indonesia’s philosophical foundation, is crucial in national identity and citizen development. However, traditional teaching methods are less effective in engaging the digital-era youth. The Pancasila Ideology Development Agency (BPIP) has introduced hybrid learning, combining face-to-face and online methods, which offers flexibility, increased accessibility, and enhanced engagement. Despite these advantages, challenges such as increased workload for educators, technical issues, and the need for effective course design persist. Utilizing the Technology Acceptance Model (TAM), which emphasizes perceived usefulness and ease of use, can enhance hybrid learning environments. The study employs a comprehensive library research methodology, analyzing recent literature to identify recurring themes and gaps. Findings highlight the potential of hybrid models to make Pancasila education more relevant and engaging while addressing the need for innovative teaching strategies and technological support. Recommendations are provided for educators and policymakers to effectively implement hybrid Pancasila training, fostering a deeper understanding and appreciation of Pancasila values among the younger generation.